The Role Of Community In Combating The Spread Of Pornography Among Adolescents In Malaysia - Nurul Aqilah Mahmud; Izwan Suhadak Ishak; Awang Syazuan Shafiq Awang Jaya; Kamarul Azami Mohd Zaini (Proceeding International Seminar of Islamic Studies, 2019)
Addiction to pornography has always been a catalyst of serious social issues in Malaysia and all over the world ever since western countries began legalizing it decades ago. In order to tackle this menace, Wadah Pencerdasan Umat (WADAH) in collaboration with Centre for Community Engagement and Student Movement (COMNET) of Universiti Selangor has initiated a pornography-prevention module titled Sekeluarga Tolak Pornografi (STOP) that aims to tackle the early prevention of pornography, especially among adolescents and children. This module has and will continue to be implemented throughout the community, especially at school. Its concept is based on informative speeches by experts and interactive group activities that are guided by trained facilitators.